Dual Communication of Confluence of Total Anomalous Pulmonary Venous Connection: An Interesting but a Rare Entity - Agrawal, Gaurav (Heart Views, 2018)
Here, we describe case of a 9-month-old male child who was diagnosed with a very unusual and rare variety of mixed total anomalous pulmonary venous connection.